Analisis Potensi Bahaya Dengan Metode Hazard Identification and Risk Assesment dan Failure Mode Effect Analysis Pada PT.XYZ - Muhammad Riski Biarto; Elly Ismiyah; Akhmad Wasiur Rizqi (Fakultas Teknik, 2023)
PT. XYZ is a manufacturing company that specializes in making food and soft drinks. According to the company, there have been no reports of incidents during the production process. However, based on empirical findings obtained from observations in the maintenance section, especially in the field of assembly work, many near misses or near misses occur during the implementation stage. Efforts that need to be made to overcome this are by identifying activities that are at risk of causing work accidents. In this research, work accidents were identified using the HIRA method, which then based on the results of the HIRA, improvements were then carried out based on priorities using the FMEA methodology. In the grinding machine assembly process, it is known that there are six work activities including material selection, grinding, welding, painting, assembly, and machine trial. The HIRA identification results show that there are 8 activities that have a medium risk of work accidents, for which FMEA analysis will be carried out. The results of the FMEA analysis show that the motor selection activity for the grinding drive has the highest RPN value so the control in the work is carried out using the help of a chain block, ensuring the chain block is in prime condition, using complete personal protective equipment, carrying out work according to SOP, and using chain block according to capacity.